THE CONCEPTUAL BASES OF REGIONAL SUSTAINABLE DEVELOPMENT MANAGEMENT - Богуславська, Світлана (Socio-economic relations in the digital society, 2019)
The article is devoted to the analysis and improvement of the regional management theoretical concept. Author’s proposals were elaborated taking into account the need of providing the sustainable development of the region. Modern directions of formation of the global world economic, information, fi nancial space defi ne fundamentally new tasks for the formation and development of forms and methods of management of regional systems. These circumstances required elaborating and implementation of the innovative forms, methods and tools for regional development, as well as improvement of regional management organization and technologies, transformation of the state regional policy. Th e basic defi nitions of regional management as the regional system, regional policy, the region’s self-development,sustainable development of the region were clarifi ed and complemented at the article. The role and place of the region in the national economic space were substaintiated. It was determined, that the most important of the theoretical and practical part of the regional management is strategic planning. The main components, stages, elements, forms of strategic planning, as well as specialized legislative acts that regulate the activities of regional authorities on strategic planning were presented. Th e main tendencies and shortcomings of the strategic planning’s practice of at the regional level were determined. Th e necessity to consider the strategy of regional sustainable development as a complex ofinterconnected independent components was substantiated. It consist the concept of development, a macro model of the development strategy and complex target strategies.